ICTs as a Distinct Detection Approach for Dyslexia Screening: A Contemporary View - Athanasios S. Drigas (International Journal of Online and Biomedical Engineering, 2019)
In contemporary times, various studies have been conducted around the world, researching the use of Information and Communication Technologies (ICTs) on dyslexia screening in all ages. Screening procedure constitutes the first vital step to investigate the kind of these experiencing difficulties, which sets the foundations for a well-designed intervention. Thus, ICTs is becoming an emerging unique supplementary strategy, using cost-effective and easy to access advanced tests for gaining in-depth knowledge about students’ learning profiles. The purpose of this literature review is to present an indicative number of digital assessment tools (e.g. computerized systems, software, applications etc.) for detecting dyslexia, that have been designed or have been implemented on dyslexic population during the last thirteen years (2005-2018). The classification of proposed papers has been carried out according to the life stage, each of whom analyzed.